2008
DOI: 10.1007/s00330-008-1099-2
|View full text |Cite
|
Sign up to set email alerts
|

Can abdominal multi-detector CT diagnose spinal osteoporosis?

Abstract: The aim of this study was to (1) generate quantitative CT (QCT) densitometric data based on routine abdominal multi-detector (MDCT) examinations and (2) investigate whether these data can be used to differentiate osteoporotic from healthy females. Twenty-five female patients (group A) with a history of radiotherapy were examined both with routine abdominal MDCT and standard QCT to generate a MDCT-to-QCT conversion equation. Twenty-one osteoporotic (group B) and 23 healthy female patients (group C) were also re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 13 publications
1
22
0
2
Order By: Relevance
“…13,14 In previous studies, it has been demonstrated that routine contrast-enhanced and non-contrast-enhanced abdominal CT as well as cardiac CT scans may be used to determine BMD of the spine. 13,14,[23][24][25][26] We have developed 2 MDCT-to-qCT conversion equations for 120 kVp and 140 kVp tube voltage, respectively, which both show a high correlation coefficient and are comparable with previous studies. 13,14 To our knowledge, there were 3 aspects that have been analyzed in this study for the first time: First, we were able to confirm converted BMD values obtained from MDCT scans as prognostic markers for screw loosening in patients with spondylodesis.…”
Section: Discussionsupporting
confidence: 72%
“…13,14 In previous studies, it has been demonstrated that routine contrast-enhanced and non-contrast-enhanced abdominal CT as well as cardiac CT scans may be used to determine BMD of the spine. 13,14,[23][24][25][26] We have developed 2 MDCT-to-qCT conversion equations for 120 kVp and 140 kVp tube voltage, respectively, which both show a high correlation coefficient and are comparable with previous studies. 13,14 To our knowledge, there were 3 aspects that have been analyzed in this study for the first time: First, we were able to confirm converted BMD values obtained from MDCT scans as prognostic markers for screw loosening in patients with spondylodesis.…”
Section: Discussionsupporting
confidence: 72%
“…Papadakis et al [21] showed that BMD measurements could be used as a diagnostic tool for osteoporosis. However, both studies only used contrast-enhanced CT and did not compare these findings with unenhanced measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Experience already exists with phantomless BMD measurements in the lumbar spine (21) and comparisons of lumbar and thoracic phantom-based BMD measures (22).…”
Section: Discussionmentioning
confidence: 99%